2010
DOI: 10.12693/aphyspola.117.374
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Behaviour of Core/Shell Nanoparticle Assemblies: Interparticle Interactions Effects

Abstract: Interparticle interactions in assemblies of nanoparticles represent an important effect that modifies their magnetic behavior. The characteristics of the hysteresis loop and the temperature dependent magnetization (field cooled (FC)/zero-field cooled (ZFC)) are studied numerically in magnetic nanoparticle assemblies using Monte Carlo simulations and the standard Metropolis algorithm. We study composite spin nanostructures with ferromagnetic (FM) core/antiferromagnetic (AFM) shell morphology and simple ferromag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…According to the literature, when magnetic nanoparticles are close enough they exhibit dipolar interactions that modify their magnetic properties. For disordered ensembles of nanoparticles, these interactions commonly induce an increase of the coercivity, as we observed here . However, for ordered ensembles of nanoparticles it has been found that dipolar interactions reduce the coercivity, which is consistent with our present observations. , This effect described in literature is also observed in our ordered assemblies. When the magnetic moment of a nanoparticle is reversed, it triggers the reversal process of the neighboring nanoparticles through dipolar interactions; these interactions are such that the 134-nm polymer-COA (sample F) require smaller fields for saturation than the conventional MNBs (sample E) and the COAs (samples H and G).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…According to the literature, when magnetic nanoparticles are close enough they exhibit dipolar interactions that modify their magnetic properties. For disordered ensembles of nanoparticles, these interactions commonly induce an increase of the coercivity, as we observed here . However, for ordered ensembles of nanoparticles it has been found that dipolar interactions reduce the coercivity, which is consistent with our present observations. , This effect described in literature is also observed in our ordered assemblies. When the magnetic moment of a nanoparticle is reversed, it triggers the reversal process of the neighboring nanoparticles through dipolar interactions; these interactions are such that the 134-nm polymer-COA (sample F) require smaller fields for saturation than the conventional MNBs (sample E) and the COAs (samples H and G).…”
Section: Resultssupporting
confidence: 93%
“…26 However, for ordered ensembles of nanoparticles it has been found that dipolar interactions reduce the coercivity, which is consistent with our present observations. 27,29 This effect described in literature is also observed in our ordered assemblies. When the magnetic moment of a nanoparticle is reversed, it triggers the reversal process of the neighboring nanoparticles through dipolar interactions; these interactions are such that the 134-nm polymer-COA (sample F) require smaller fields for saturation than the conventional MNBs (sample E) and the COAs (samples H and G).…”
Section: ■ Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The main problem which we would like to resolve is the surface and interlayer structure and their influence on the core properties of nanoparticles. A very interesting area which should be studied is the interlayer interaction between the core and the shell inside each separate nanoparticle (intra-particle interaction) apart from the better established inter-particle interaction [23].…”
Section: Introductionmentioning
confidence: 99%
“…The dipole-dipole energy between two magnetic moments depends on de the magnetic domains (nanoparticles) moment and the distance between them, as is widely described in the literature. [23][24][25] Nevertheless, from the simplified dipolar interaction, one may assume the magnetic interaction energy E is proportional to M i · M j where M i and M j are magnetic moments of magnetic two nearest neighbors. 26 However, in order to consider not only the nearest neighbor, but also the total system contribution, a model considering the interaction of each nanoparticle with the others is implemented.…”
Section: Model Descriptionmentioning
confidence: 99%